Judges’ Considerations in Deciding Illegal Mining Cases: A Study of Decision Number 237/Pid.Sus/2025/PN Tjk - Tasya Balqis Uftimentari; Tami Rusli; Risti Dwi Ramasari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Illegal mining is a criminal act in the mining sector that causes state losses and has an impact on environmental damage and social life of the community. In law enforcement, judges have an important role in making decisions by considering the legal aspects and socio-economic conditions of the perpetrators. This study aims to determine the factors causing the crime of illegal mining in Pesawaran Regency and the judge's considerations in deciding the case based on Decision Number: 237/Pid.Sus/2025/PN TJK. The research method used is normative and empirical juridical with data obtained through literature studies and interviews. The results of the study indicate that the factors causing illegal mining include economic factors, low legal awareness, complicated licensing processes, weak supervision, and high market demand for illegal mining products. The judge's considerations are based on trial facts, fulfillment of the elements of the crime, evidence, as well as the defendant's socio-economic conditions and the environmental impacts caused. Thus, the judge's considerations not only focus on legal certainty but also pay attention to aspects of justice and legal benefits.